Moringa oleifera Leaf Extract Protects C2C12 Myotubes against H2O2-Induced Oxidative Stress - Roberta Ceci; Mariateresa Maldini; Mark E. Olson; Domenico Crognale; Katy Horner; Ivan Dimauro; Stefania Sabatini; Guglielmo Duranti (Antioxidants, 2022)
The imbalance between reactive oxygen species (ROS) production and antioxidant defense systems leads to macromolecule and tissue damage as a result of cellular oxidative stress. This phenomenon is considered a key factor in fatigue and muscle damage following chronic or high-intensity physical exercise. In the present study, the antioxidant effect of Moringa oleifera leaf extract (MOLE) was evaluated in C2C12 myotubes exposed to an elevated hydrogen peroxide (H2O2) insult. The capacity of the extract to influence the myotube redox status was evaluated through an analysis of the total antioxidant capacity (TAC), glutathione homeostasis (GSH and GSSG), total free thiols (TFT), and thioredoxin (Trx) activity, as well as the enzyme activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) and transferase (GST). Moreover, the ability of MOLE to mitigate the stress-induced peroxidation of lipids and oxidative damage (TBARS and protein carbonyls) was also evaluated. Our data demonstrate that MOLE pre-treatment mitigates the highly stressful effects of H2O2 in myotubes (1 mM) by restoring the redox status (TFT, Trx, and GSH/GSSG ratio) and increasing the antioxidant enzymatic system (CAT, SOD, GPx, GST), thereby significantly reducing the TBARs and PrCAR levels. Our study provides evidence that MOLE supplementation has antioxidant potential, allowing myotubes better able to cope with an oxidative insult and, therefore, could represent a useful nutritional strategy for the preservation of muscle well-being.